Dialogic literary argumentation and close reading: effects on high school students’ literature-related argumentative writing and motivational beliefs - Fulton, Kevin; Lin, Tzu-Jung; Newell, George (Frontiers in Psychology, 2023)
Given evidence that adolescent students' motivation to read and write about literature declines with age, we proffer an approach called Dialogic Literary Argumentation (DLA) that asks students to explore literature through argumentation in pursuit of understanding the meanings and possibilities of being human. This quasi-experimental study compared the effectiveness of DLA with close reading (CR), a common approach to teaching literature in high school English language arts classrooms, in improving students' motivational beliefs about writing and literature-related argumentative writing. The study also examined how the links between motivational beliefs and argumentative writing performance varied by instructional contexts. Participants were 278 high school students in 14 classrooms across 8 public high schools. Classrooms of students received either DLA or CR throughout the academic year. While both the DLA and CR groups improved in literature-related argumentative writing, the DLA group demonstrated more growth than the CR group. Neither group exhibited changes in motivational beliefs. However, at the end of the year, both DLA and CR students' transactional writer beliefs were predictive of writing self-efficacy.Transmissional writer beliefs negatively correlated with argumentative writing in the CR group and had a null relationship in the DLA group. Overall, motivational beliefs and argumentative writing were more positively correlated in the DLA group than the CR group after the intervention. We posit that the argumentative elements unique to DLA may act to protect students from the negative impacts of transmissional beliefs. Our findings provide theoretical explanations and pedagogical recommendations on how DLA and CR can be jointly employed to heighten students' motivation and strengthen their argumentative writing competence.